PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN, RESIKO DAN REGULASI UNTUK MELAKUKAN TRANSAKSI PINJAMAN DANA MENGGUNAKAN PLATFORM FINANCIAL TECHNOLOGI (FINTECH) PEER TO PEER (P2P) LENDING DANAMAS DI KOTA DENPASAR - Ni Kadek Rika Evimalia; Ni Wayan Alit Erlina Wati (Hita Akuntansi dan Keuangan, 2022)
This study aims to determine "Perceptions of Ease of Use, Risk and Regulation on Decisions to Make Fund Transactions Using Financial Technology (Fintech) Peer to Peer (P2P) Lending Platforms". This research was conducted in the city of Denpasar with P2P lending users as research subjects. The sample in this study were 100 respondent with the sampling technique used was the Slovin formula. The data analysis technique used is multiple linear regression analysis techniques. The results of this study indicate that perceived ease of use has a positive effect on loan transactions using the Peer to Peer (P2P) Lending Platform FinancialTechnology (Fintech). Perception of risk has a positive effect on lending transactions using the Peer to Peer (P2P) Lending Platform Financial Technology (Fintech). The regulation has a positive effect on lending transactions using the Peer to Peer (P2P) Lending Platform Financial Technology (Fintech